Pengaruh E-Wom Dan Kualitas Produk Terhadap Keputusan Pembelian Dan Minat Beli Ulang: Survei Pada Pengguna Kosmetik Hanasui Di Kecamatan Grati - Suci Armanis (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This study aims to determine the effect of Electronic Word Of Mouth and Product Quality on Purchase Decision and Repurchase Interest in Hanasui Cosmetic Products. The independent variables used are Electronic Word Of Mouth (X1) and Product Quality (X2) variables, while the dependent variables used are Purchase Decision (Y1) and Repurchase Intention (Y2). This research uses explanatory research using a quantitative approach. The sample in this study amounted to 198 respondents to purchasing decisions and repurchasing intentions among consumers who use Hanasui cosmetics in Grati District. The sampling technique uses purposive sampling technique and the data collection technique uses a questionnaire. The data analysis technique used is instrument testing (validity test and reliability test). The results of the research based on the analysis of the coefficient of determination are used to calculate the magnitude of the influence of the independent variables on the dependent variable. From the analysis, the results obtained are R² (coefficient of determination) of 0.327, which means that electronic word of mouth and product quality are able to explain their influence on purchasing decisions. Furthermore, repurchase intention is 0.327 which means that electronic word of mouth, product quality, and purchasing decisions are able to explain the effect on repurchasing intention of Hanasui products.